Impacts of pricipitation and temperature variability on rice production in Mitole Epa Chikwawa - Phiri, Charles (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Rainfall and temperature variability are a threat to sustainable agricultural production in Malawi. Main crops which include rice are highly affected due to climate variability since this crop is grown during wet season. A study was therefore conducted in one EPA named Mitole in Chikwawa district in southern Malawi to determine the impacts of precipitation and temperature variability on rice production. Method: Secondary data of climate variables and rice data was used for a period of 16 years which was obtained from Department of Climate Change and Meteorological Services (DCCMS) in Blantyre and Mitole EPA in Chikwawa respectively. Before data analysis data quality control was done where outliers were manually corrected and also errors were corrected using homogeneity test in which single mass curve for each data were plotted. In data analyses; excel and R was used to do trend analysis. Mann Kendall test was used to test if there were significant trend of data or not. To determine the relationship between climate parameters and rice production correlation analysis tested. Regression analysis was also used to predict the results if the climate variables keep varying. Findings: The results showed that only minimum temperature had a negative significant trend and other variables had trends which were not significant. Correlation analysis showed non-significant relationship between climate parameters and rice production and also the results of regression analysis had non-significant relation therefore there was enough evidence to predict the results in future. Conclusion: Since the results did not provide enough evidence that climate variables specifically rainfall and temperature affect rice production in the area, it was recommended that more research must be done to discover the way farmers must follow to maximize the production. Novelty/Originality of this study: This study provides concrete data on the impacts of climate variability on rice production in southern Malawi, which farmers and policymakers can use to develop more effective agricultural adaptation strategies in the region.